2016
DOI: 10.1002/col.22052
|View full text |Cite
|
Sign up to set email alerts
|

A new device color gamut boundary description algorithm based on irregular segmentation

Abstract: The description of device color gamut is very important for color gamut mapping, which plays an important role in cross‐media color reproduction. To get a more accurate color gamut boundary, several gamut boundary description (GBD) methods have been presented in the past; however, many problems still exist in the current algorithm (e.g., accuracy and speed). In this study, we propose a new device GBD method based on irregular segmentation and evaluate it against other GBD algorithms. In the irregular segmentat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…This investigation was longitudinal because the research question was posed with regard to students' conceptual development over time (Creswell, 2013). A qualitative exploratory case study design was implemented because it allowed in-depth examination on reasoning about variability and the changes over time (Yin, 2017). Ten college students participated in the study.…”
Section: Methodsmentioning
confidence: 99%
“…This investigation was longitudinal because the research question was posed with regard to students' conceptual development over time (Creswell, 2013). A qualitative exploratory case study design was implemented because it allowed in-depth examination on reasoning about variability and the changes over time (Yin, 2017). Ten college students participated in the study.…”
Section: Methodsmentioning
confidence: 99%
“…An important point was the choice of multiple and not unique case studies in this investigation. Precisely because we are not facing a classic context, in which the conditions of the business environment are previously known or established, the adoption of multiple study cases as indicated by Yin (2017) allows us to offer more comparative situations of analysis, thus contributing to increase the reliability in the triangulation of the material produced. The recommendations of Yin (2017) regarding the reliability and robustness aspects of the analysis through multiple study cases were also followed: (i) the validity of the construct through the definition of a protocol for the conduct of the study cases and semi-structured interviews; (ii) the internal validity through the understanding of the interdependence between the emergence of the GDPR and the need to adapt the interfaces to comply with the rules imposed by the GDPR; (iii) the external validity through the replication of the study in four companies; and (iv) the reliability through the collection of information from each company and discussion of the adopted practices.…”
Section: Methodsmentioning
confidence: 99%